Competências essenciais norteadoras para o perfil do gestor estratégico em Instituições de Ensino Superior - Oliveira Filho, Raimundo Olavo de (2013)
The main objective that guided the development of the study it was to verify the necessary competences for a manager of higher teaching, the way for which he can manage this level of education rightly. The secondary objectives involve to identify knowledge, ability and attitude of managers of the kind of institution focused; also to observe the competences that are the most present in these professionals and to know the manager profile to suggest what could be the ideal portrait of a manager. This empirical research focuses on the following typologies: descriptive, bibliographic and fieldwork, its character is quali-quantitative, based on the idea of management competences and attributes: knowledge, ability and attitude. Concerning the results, this research reached the proposed objectives and it is possible to say that the managers know what is required for directing a higher teaching institution, information proved by the level of agreement of these professionals with the competence attributes: knowledge, ability and attitude, but are few the managers with specific capacities to conduct the institutions. Thus, we realize that there is little experience but inappropriate formation for the studied role, although these managers are successful in their action field. This study, related to the essential competences that take to the profile of the strategic manager in higher teaching institutions, suggests the model of management by competence in the same institutions.